Automatic change detection: Mismatch negativity and the now-classic Rensink, O’Reagan, and Clark (1997) stimuli - File, Domonkos; Petro, Bela; Gaál, Zsófia Anna; Csikós, Nóra; Czigler, István (Frontiers in Psychology, 2022)
Change blindness experiments had demonstrated that detection of significant changes of natural images are extremely difficult when brief blank fields are placed between alternating displays of an original and a modified scene. On the other hand, research on the visual mismatch negativity component (vMMN) of the event-related potentials (ERPs) identified sensitivity to events (deviants) different from the regularity of stimulus sequences (standards), even if the deviant and standard events are non-attended. The present study sought to investigate the apparent controversy between the experiences under the change blindness paradigm and the ERP results. On this end, the stimuli of Rensink, O’Reagen and Clark (1997) was adapted to a passive oddball ERP paradigm to investigate the underlying processing differences between the standard (original) and deviant (altered) stimuli measured at 22 subjects. A posterior negativity within the 280-330 ms latency range emerged as the difference between ERPs elicited by standard and deviant stimuli, identified as visual mismatch negativity (vMMN). These results raise the possibility that change blindness is not based on the lack of detailed visual representations or the deficiency of comparing two representations. However, effective discrimination of the two scene versions requires considerable frequency differences between them.